Peranan Guest Relation Officer dalam Meningkatkan Kepuasan Tamu di Hotel Grand Elite Pekanbaru - Sri Febdarina; Aldi Julianto; Maryantina Maryantina; Lisa Lestari; Asur Suryana (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Service quality is a key factor that determines guest satisfaction and loyalty in the hospitality industry. Guest Relations Officers (GROs) play an important role as liaisons between guests and hotel management, especially in creating personalized and memorable stays. This study aims to analyze the role of GRO in improving guest satisfaction at the Grand Elite Hotel in Pekanbaru. The research method used is descriptive with a mixed methods approach, namely qualitative through observation and in-depth interviews with the Front Office Manager and GRO staff, and quantitative through the distribution of questionnaires to 95 hotel guests.This study was conducted at the Grand Elite Hotel in Pekanbaru from February to May 2023. Service analysis was carried out based on the five dimensions of SERVQUAL service quality, namely reliability, responsiveness, assurance, empathy, and tangibles. The results showed that GRO service quality was in the “good” category with an average score of 4.03, while guest satisfaction reached 4.14. The tangibles dimension received the highest score, while responsiveness received the lowest score due to limited staff numbers and overlapping duties between GRO and receptionists. These findings highlight the importance of increasing the number and competence of GRO staff so that service can be provided optimally and consistently. It is recommended that hotel management restructure the Front Office and provide ongoing training for GRO staff to strengthen guest satisfaction and loyalty on an ongoing basis.